Why the Debate on Proportionalism is Misconceived - Quirk, Michael J. (Modern theology, 1997)
Proportionalists and anti-proportionalists assume that, insofar as moral description is a problem, the solution is a theory of moral description. McCormick and Finnis (as well as John Paul II) are test-cases for showing this. However, both sides neglect the primacy of moral practice. Disputes about moral description can be recast as disputes about practices and virtues, leaving aside the whole conceptual apparatus of the proportionalism debate.